Breakthrough discoveries in information technology research : advancing trends - Khosrowpour, Mehdi, 1951- (Hershey, PA : Information Science Reference, 2010)
'This book informs researchers and practitioners of novel and emerging research in information science and technology, allowing for the discussion and dissemination of critical concepts that will promote further study and innovation'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Information technology -- technological innovations; Information technology -- Research; Offshore outsourcing